24.7k views
3 votes
Determine the two ordered pair solutions of the equation y = 2x2 + 3x , given (0, ), and (-2, ).

User Will Green
by
5.1k points

1 Answer

1 vote

Answer:

We conclude that the two ordered pairs (0, 0) and (-2, 2) are the solutions of the equation y = 2x² + 3x.

Explanation:

Given the expression

y = 2x² + 3x

Substituting x = 0

y = 2(0)² + 3(0)

y = 0+0

y = 0

  • so when x = 0, y = 0

Thus, the ordered pair is: (0, 0)

Now, substituting x = -2

y = 2x² + 3x

y = 2(-2)² + 3(-2)

y = 8 - 6

y = 2

  • so when x = -2, y = 2

Thus, the ordered pair is: (-2, 2)

Therefore, we conclude that the two ordered pairs (0, 0) and (-2, 2) are the solutions of the equation y = 2x² + 3x.

User Alexander Popov
by
5.1k points